A Comparison of the Implementation of Presidential Impeachment in Presidential Systems (A Comparative Study of Indonesia and South Korea) - Syalsabila, Khairunisa; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Constitution (UUD) is the supreme law that serves as the basis for the administration of the state and must be obeyed by all elements of the nation, including the President and Vice President. In a presidential system of government, the President's extensive executive power demands a strict oversight mechanism, one of which is through impeachment. This study aims to analyze and compare the legal regulations and implementation mechanisms for the impeachment of heads of state in Indonesia and South Korea. The study uses a literature study method with a qualitative approach through analysis of various legal sources, journals, and relevant literature. The results show that Indonesia regulates impeachment in detail in Articles 7A and 7B of the 1945 Constitution with the involvement of the House of Representatives (DPR), the Constitutional Court, and the People's Consultative Assembly (MPR), and the reasons for impeachment are specifically outlined. Meanwhile, South Korea regulates impeachment in its Constitution more generally by involving the National Assembly and the Constitutional Court, and is not limited to the President, but also other high-ranking state officials. In practice, South Korea has successfully implemented the impeachment process constitutionally, while Indonesia has never implemented this mechanism in accordance with the procedures following the amendment to the 1945 Constitution. In conclusion, although both countries adopt a presidential system of government, there are significant differences in the legal structure, grounds for impeachment, and implementation of the impeachment mechanism.